The Integration of AI and IoT in Cyber-Physical Systems for Smart Manufacturing in Indonesia - Wardhani, Diky; Simarangkir, Manase Sahat H; Safarudin, Muhamad Sigid; Vandika, Arnes Yuli; Kaaffah, Faiz Muqorrir (Eastasouth Institute, 2025)
The integration of Artificial Intelligence (AI) and the Internet of Things (IoT) within Cyber-Physical Systems (CPS) represents a transformative opportunity for smart manufacturing in Indonesia. This study employs a qualitative approach, with insights from five informants, to explore the current state, challenges, opportunities, and strategic recommendations for CPS adoption. Findings reveal that while CPS adoption is in its early stages, it has significant potential to enhance operational efficiency, sustainability, and global competitiveness. Challenges such as limited infrastructure, skill gaps, and cybersecurity concerns are prevalent. However, opportunities exist in leveraging government initiatives, fostering local innovation, and promoting sustainability. Strategic recommendations include enhancing digital infrastructure, providing financial incentives, upskilling the workforce, and establishing clear regulatory frameworks. These insights contribute to advancing Indonesia's Industry 4.0 agenda and offer a roadmap for stakeholders to navigate CPS integration effectively.